2020
DOI: 10.1155/2020/5483981
|View full text |Cite
|
Sign up to set email alerts
|

The Monocyte-to-Lymphocyte Ratio at Hospital Admission Is a Novel Predictor for Acute Traumatic Intraparenchymal Hemorrhage Expansion after Cerebral Contusion

Abstract: Purpose. To explore the potential of monocyte-to-lymphocyte ratio (MLR) at hospital admission for predicting acute traumatic intraparenchymal hematoma (tICH) expansion in patients with cerebral contusion. Patients and Methods. This multicenter, observational study included patients with available at-hospital admission (baseline) and follow-up computed tomography for volumetric analysis (retrospective development cohort: 1146 patients; prospective validation cohort: 207 patients). Semiautomated software assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 49 publications
2
20
2
Order By: Relevance
“…In this study, CC sites were included, including frontal lobe, parietal lobe, temporal lobe and occipital lobe. Statistical results showed that the differences were not statistically significant(P>0.05), which was inconsistent with previous reports [ 24 ]. We analyzed the reasons as follows: Basal ganglia and brain stem or cerebellum is human body important vital center, once the damage prognosis is poor, but we are all included in patients with contusion parts above the tentorium, if not acute oppression brain stem hemorrhage or edema, generally will not endanger the patient lives, usually only can cause injury of brain tissue function is impaired, leaving related sequelae.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, CC sites were included, including frontal lobe, parietal lobe, temporal lobe and occipital lobe. Statistical results showed that the differences were not statistically significant(P>0.05), which was inconsistent with previous reports [ 24 ]. We analyzed the reasons as follows: Basal ganglia and brain stem or cerebellum is human body important vital center, once the damage prognosis is poor, but we are all included in patients with contusion parts above the tentorium, if not acute oppression brain stem hemorrhage or edema, generally will not endanger the patient lives, usually only can cause injury of brain tissue function is impaired, leaving related sequelae.…”
Section: Discussioncontrasting
confidence: 99%
“…In patients with CC, monocytes, neutrophils and lymphocytes can invade from the periphery and participate in the injury response without the control of the BBB. Sheng et al [ 24 ] established a prediction model of cerebral rebleeding risk after craniocerebral injury, and concluded that MLR had a great predictive value for the expansion of acute traumatic parenchymal hematoma. Therefore, this study included MLR as a variable in the study to explore its predictive value for the prognosis of patients with CC.…”
Section: Discussionmentioning
confidence: 99%
“…A high MLR may indicate a high level of intracerebral monocyte infiltration in patients with brain contusion. Given its easy accessibility, this indicator may provide new insights into neuroinflammation for promoting acute tICH expansion [18]. Consistent with its performance in the development dataset, the TPHEA nomogram maintained optimal discrimination and good calibration in an external validation dataset.…”
Section: Discussionmentioning
confidence: 57%
“…Several small retrospective studies have attempted to develop comprehensive models for tICH expansion based on clinical and imaging variables [ 11 , 15 , 16 ]. However, some crucial predictors were not considered, including baseline tICH volume, a novel imaging marker of multihematoma fuzzy sign, and an inflammatory marker of monocyte-to-lymphocyte ratio (MLR) [ 17 , 18 ]. In addition, the predictive value of these models must be verified in a large multicenter sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Jan et al also found that MLR can be used as a prognostic factor for malignancy [78]. Sheng et al suggested that MLR is a predictor of the inflammatory process and the risk of hematoma expansion in cases of cerebral contusion after brain injury [79]. In stroke patients, MLR was reported associated with depression occurrence within 3 months [80].…”
Section: Monocyte-to-lymphocyte Ratio (Mlr)mentioning
confidence: 99%